Lockdown of colleges and universities due to COVID-19: Any impact on the educational system in India? - Ravi Chandra Ravi (Wolters Kluwer Medknow Publications, 2020)
Pneumonia triggered by novel corona virus (SARS-CoV-2) in Wuhan, China, in December 2019 is an extremely contagious disease. The WHO has stated the outbreak of COVID-19 (corona virus) as a pandemic issue. Corona virus cases started increasing day by day in India, also from the time the first case was diagnosed on January 30, 2020. In this regard, there are so many colleges and universities across India which cancelled or rescheduled their academic activities such as conferences, workshops, and other academic and sports activities. Because the universities and colleges should protect and take care of their students and faculty in this regard. In this brief communication, I would like to give an idea on the potential impact of the dangerous COVID-19 outbreak on the education system and mental health of students and staff.